Association of the Trough, Peak/Trough Ratio of Imatinib, Pyridine–N-Oxide Imatinib and ABCG2 SNPs 34 G>A and SLCO1B3 334 T>G With Imatinib Response in Egyptian Chronic Myeloid Leukemia Patients - Omran, Mervat M.; Abdelfattah, Raafat; Moussa, Heba S.; Alieldin, Nelly; Shouman, Samia A. (Frontiers in Oncology, 2020)
Abstract Imatinib mesylate (IM) is highly efficacious in the treatment of Chronic Myeloid Leukemia (CML). Therapeutic drug monitoring and pharmacogenetic screening are warranted for better management of imatinib therapy. The goal of this study was to gain a greater mechanistic understanding of the factors governing variable imatinib level and its relationship to response. One hundred and two patients with CML at chronic phase were recruited in this study. Blood samples were withdrawn at least 30 days after drug administration, trough and peak concentrations of imatinib, N-des-methyl imatinib, and pyridine–N-oxide imatinib were determined by HPLC/MS/MS. Genetic polymorphism of the genes ABCG2 SNPs 34 G>A and 421C >A; ABCB1 SNPs 2677 G>A/T, 1236 C>T, 3435C>T; SLCO1B3 SNPs T334G and CYP3A5 were studied using PCR-RFLP technique. Our study presented significant higher trough IM (1281 ± 578 ng/ml), lower Peak/Trough ratio, clearance (Cl), and elimination rate constant, ke, among patients who achieved good responses (N = 64) than those for patients who suffered unfavorable response (N=37). The P/T ratio was the only significant independent factor affecting response, as the P/T ratio increased by one, the risk of bad response increased by more than double as compared to good response with 95% CI (1.28 – 3.92, P = 0.005). Moreover, like the results of IM, the trough concentration of Pyridine-N-oxide imatinib was significantly higher (P=0.01) and its P/T ratio was significantly lower (P=0.008) in patients achieved favorable response than those without. The wild GG genotype of the ABCG2.G34A gene was associated with favorable response (P=0.01), lower Cl, Ke and high plasma IM trough level than both (AA+GA) genotypes. While ABCG2 C421A (CC) genotype had a significantly higher plasma peak of IM, N-des-methyl imatinib and higher Css. The GG and TG alleles of the SLCO1B3.T334G gene were significantly correlated to favorable response, while the wild allele TT was linked to unfavorable response (p=0.03). In conclusion, the trough and P/ T ratio for both IM and Pyridine-N-oxide imatinib, in addition to Polymorphism of ABCG2 SNPs 34 G>A and SLCO1B3. T334G gene is a good predictor for response of IM in CML Egyptian patients.